Application of α-lipoic acid beyond peripheral diabetic polyneuropathy (A report of 3 cases) (Medical Journal of Indonesia, 2011)
Background: In Germany, lipoic acid is registered with the indication of "peripheral diabetic polyneuropathy". This report intends to demonstrate therapeutic activity beyond this indication. In Indonesia, the substance is not registered for therapy. Methods: Three patients (two of them in Germany and one in Indonesia) with pathoneurological symptoms differentÂ from peripheral diabetic polyneuropathy were treated with α-lipoic acid: i) post-borelliosis inflammation with arthritic and paraesthetic symptoms, ii) post-operative (mamma carcinoma) and post-chemotherapeutic sensoric and motoric neural deficits occurring in parallel with additional radiation therapy, and iii) post-traumatic (cerebral) and postoperative (brain surgery) cardiovascular and pulmonary crisis with broad pathoneurological (sensoric and motoric, visual, auditory) deficits and dysarthria. Results: All three patients improved in close correlation with the onset and continuation of lipoic acid intake, whereas other therapeutic measures did not appear very successful. It cannot be ruled out that the other therapeutic regimens applied interacted with lipoic acid in a supporting additive or synergistic manner, because three cases as reported here do not allow for such conclusion; however, separately, or with interaction, lipoic acid helped the patients to recover from their pathoneurological symptoms in the meaning of the traditional medical term "restitutio ad integrum". Conclusion: In the three cases in this study, lipoic acid was effective in therapy of pathoneurological symptoms different from peripheral diabetic neuropathy. Further confirmative studies are suggeted. (Med J Indones 2011; 20:143-8)